(untitled) - Lori (Thành phố Hồ Chí Minh, 2009)
TNT TOEIC, Introductory Two, is intended for fre-intermediate learners target TOEIC score is in the range of 350 - 400. The book consists of 20 listening units and 20 reading units, with focus on TOEIC listening testing points practice and basic grammar items to help learners at this level tackle the test with some confidence. The grammar such as nouns, pronouns, adverbs, subject-verb agreement and basic verb patterns.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Study guides,Textbooks for foreign speakers,Hướng dẫn học tập,Sách giáo khoa cho người nước ngoài